2013
DOI: 10.1002/bies.201300072
|View full text |Cite
|
Sign up to set email alerts
|

Jumping the fine LINE between species: Horizontal transfer of transposable elements in animals catalyses genome evolution

Abstract: Horizontal transfer (HT) is the transmission of genetic material between non-mating species, a phenomenon thought to occur rarely in multicellular eukaryotes. However, many transposable elements (TEs) are not only capable of HT, but have frequently jumped between widely divergent species. Here we review and integrate reported cases of HT in retrotransposons of the BovB family, and DNA transposons, over a broad range of animals spanning all continents. Our conclusions challenge the paradigm that HT in vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 78 publications
1
46
0
Order By: Relevance
“…This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 78%
See 1 more Smart Citation
“…This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 78%
“…HT of TEs (HTT) may allow these elements to enter naive genomes, which they invade by making copies of themselves, and then escape before they become fully silenced by anti-TE defenses (13). A growing number of studies have identified such HTT (11,[14][15][16]. However, a common drawback of these studies has been the inclusion of a limited set of TEs (11) or organisms (16), which hampers our understanding of the breadth of HTT, its contribution to genome evolution, and of the factors and barriers shaping these transfers in eukaryotes (13).…”
mentioning
confidence: 99%
“…Therefore, a viral vector of HGTs from bacteria to animals is unlikely, since to my knowledge, no virus is currently known to infect both animals and bacteria (Glansdorff et al 2009;Bilewitch and Degnan 2011;Nilsson 2014;Mihara et al 2016). However, of significance to animal HGT is that these studies show that TEs can act as vectors too, and can also transfer hitchhiking non-LTR retrotransposons that are not transfer prone (Ivancevic et al 2013). While from a different circumstance, these findings show that both MEs and genomes are dynamic and that perhaps MEs are involved in mechanisms of animal HGT -certain they have appropriate machinery.…”
mentioning
confidence: 99%
“…This proposal is further supported by findings on a related biological process -the horizontal transfer of TEs between different animal species. There is recurrent and prevalent horizontal transfer of TEs among animals including mammals and reptiles (Houck et al 1991;de Almeida and Carareto 2005;Pace et al 2008;Gilbert et al 2012;Ivancevic et al 2013;Walsh et al 2013). So ubiquitous, this horizontal transfer of TEs (HTT) is suggested a significant factor in animal genome evolution, contributing to sequence and structural variation, regulatory element modifications, and novelty Ivancevic et al 2013;Walsh et al 2013;Boto 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation